KEPUASAN NASABAH TERHADAP BANK DAN DANA PIHAK KETIGA UNIT USAHA SYARIAH BNI - Herawati, IS Eka (LPPM Universitas Terbuka, 2012)
Development of Islamic syariah banking industry still has its drawback, some of it were peoples understanding on the bank operational, narrow network, and limited skilled of human resources on syariah bank. The development of syariah bank depends on its ability to deliver excellent services to people who need product and service of Islamic syariah bank. One measure of excellent service and product is customer satisfaction. The result of this study showed that the reason in choosing BNI Syariah was not only religious factor but its quality of service which should be improved. In general, UUS BNI performance in all attributes of bank and deposit fund product have not satisfied its customers because there were still discrepancies between their actual and expected services. The most importance bank attributes according to the respondents were strategic location, branches network, credibility, professionalism, syariah ideology and hospitality. The most importance deposit fund product attributes according to the respondens were security of fund, convenience procedure of fund withdrawal, profit and loss sharing principle and technology. According to the results there were 4 (four) options of marketing strategies recommended to UUS BNI in order to be more competitive in the market. Firstly, UUS BNI has to be able to create image as Islamic and professional banking. Secondly, UUS BNI has to develop market through additional of branches. Thirdly, UUS BNI has to improve its technology by adding features on ATM technology. Fourthly, UUS BNI has to offer more attractive profit sharing.   Perkembangan perbankan syariah masih memiliki banyak hambatan, antara lain pemahaman atas operasional bank syariah, jumlah jaringan bank syariah dan keahlian sumber daya manusia dibidang bank syariah. Perkembangan perbankan syariah yang baik tergantung dari kemampuan memberikan produk dan jasa yang baik kepada nasabah. Satu ukuran tentang pemberian produk dan jasa yang baik adalah kepuasan nasabah (customer satisfaction). Hasil studi ini memperlihatkan bahwa alasan memilih bank syariah bukan hanya faktor agama, sehingga bank harus meningkatkan kualitas pelayanannya. Secara umum kinerja UUS BNI dalam semua atribut bank dan Produk Dana Pihak Ketiga belum memberikan kepuasan terhadap nasabahnya terbukti masih ada perbedaan harapan dan kenyataan. Menurut responden, atribut bank yang penting adalah lokasi yang strategis, jaringan kantor cabang, kredibilitas, profesionalisme, idiology syariah dan keramahan. Sedangkan atribut Produk Dana Pihak Ketiga yang penting menurut responden adalah keamanan dana, prosedur penarikan dana yang mudah, prinsip bagi hasil dan teknologi. Sehubungan dengan hal tersebut diatas ada 4 (empat) usulan strategi pemasaran bagi UUS BNI agar dapat kompetitif. Pertama, UUS BNI harus dapat menciptakan citra sebagai bank syariah yang profesional. Kedua, UUS BNI harus mengembangkan pasar dengan menambah jumlah kantor cabang. Ketiga, UUS BNI harus memperbaiki layanan pada teknologi ATM. Keempat, UUS BNI harus menawarkan bagi hasil yang lebih menarik melalui pembiayaan yang optimal.